BASLAWÍSH KLASS OQÍWSHÍLARÍN ZAMANAGÓY XABAR TEXNOLOGIYALARÍ MENEN OQÍTÍW ABZALLÍQLARÍ - Mırzabekova, G. (SCIENCE and SOCIETY, 2024)
This article highlights the benefits of using modern information technologies in primary school classes.